Cáncer diferenciado de tiroides, concentración sérica de hormona estimuladora de tiroides y tiroglobulina. - Gaona Bermeo, Yessenia del Cisne (2017)
Nowadays, determining biological or molecular relationships with specific neoplasms constitutes an important additional value for the individualized treatment of patients in Oncology with the purpose of detecting oncological processes in their initial stages, so that their link to less invasive techniques establishes a fundamental pillar in diagnosis. For this reason, this investigation determined the relationship between the thyroid stimulating hormone (TSH) and thyroglobulin (Tg) serum levels before and after thyroidectomy and thus the predictive value of these hormones against differentiated thyroid cancer. A retrospective, quantitative, cross-sectional group study was used, where 153 patients were evaluated, of which 64 met the inclusion and exclusion criteria. The objectives the study set out to achieve were; to determine the thyroid stimulating hormone and thyroglobulin serum levels in patients classified as tirads 3, 4 and 5 undergoing fine-needle aspiration; to define thyroid stimulating hormone and thyroglobulin serum levels after Thyroidectomy; and finally, to correlate thyroid stimulating hormone and thyroglobulin serum levels after surgical removal of the gland. The results were tabulated and statistical tests such as the Chi square, P-value and Z-value of proportions plus the interquartile relationship were carried out and presented in statistical graphs. Processing this information enabled us to determine that thyroglobulin is highly significant in the diagnosis of differentiated thyroid cancer as it presented standard deviations of 7.82 and a P-value of: 5x10-14 (0.000000000000005), the value of chi2 = 19.13. In the case of the thyroid stimulating hormone, it too was found to be highly significant with standard deviations of 3.10 and a P-value of: 1x10-2 (0.0019), the value of chi2 = 0.5818. Finally, by comparing both results, we can say that thyroglobulin has a higher predictive value than the thyroid stimulating hormone. Keywords: differentiated thyroid cancer, thyroglobulin, thyroid stimulating hormone, ultrasound classification Tirads